Acceptability and Feasibility of Real-Time Antiretroviral Therapy Adherence Interventions in Rural Uganda: Mixed-Method Pilot Randomized Controlled Trial - Musiimenta, Angella; Atukunda, Esther C; Tumuhimbise, Wilson; Pisarski, Emily E; Tam, Melanie; Wyatt, Monique A; Ware, Norma C; Haberer, Jessica E (JMIR Publications, 2018)
BackgroundWireless electronic adherence monitors can detect antiretroviral therapy (ART) adherence lapses and trigger interventions in real time, thus potentially avoiding unnecessary HIV viremia. Evidence about the acceptability and feasibility of these monitors and associated interventions, however, is limited. ObjectiveThe aim of this study was to assess the acceptability and feasibility of real-time adherence monitoring linked to text messaging (short message service, SMS) reminders and notifications to support adherence among individuals living with HIV who are taking ART in rural southwestern Uganda. MethodsIndividuals living with HIV who were initiating ART were enrolled in a pilot randomized controlled trial and followed up for 9 months. Participants received a real-time adherence monitor and were randomized to one of the following study arms: (1) scheduled SMS, (2) SMS triggered by missed or delayed doses, or (3) no SMS. SMS notifications were also sent to 45 patient-identified social supporters for sustained adherence lapses in the scheduled SMS and triggered SMS arms. Study participants and social supporters participated in qualitative semistructured in-depth interviews on acceptability and feasibility of this technology. An inductive, content analytic approach, framed by the unified theory of acceptance and use of technology model, was used to analyze qualitative data. Quantitative feasibility data, including device functionality and SMS tracking data, were recorded based upon device metrics collected electronically and summarized descriptively. ResultsA total of 63 participants participated in the study. Participants reported that real-time monitoring intervention linked to SMS reminders and notifications are generally acceptable; the predominant feedback was perceived utility-the intervention was beneficial in motivating and reminding patients to take medication, as well as enabling provision of social support. ConclusionsReal-time adherence monitoring integrated with SMS reminders and social support notifications is a generally acceptable (based primarily on perceived utility) and feasible intervention in a resource-limited country. Future efforts should focus on optimized device design, user training to overcome the challenges we encountered, cost effectiveness studies, as well as studying the monitoring aspect of the device without accompanying interventions. Trial RegistrationClinicalTrials.gov NCT01957865; https://clinicaltrials.gov/ct2/show/NCT01957865 (Archived by WebCite at http://www.webcitation.org/6zFiDlXDa)